Infinitely coherent equivalences

Content created by Egbert Rijke and maybemabeline.

Created on 2024-02-23.

{-# OPTIONS --guardedness --lossy-unification #-}

module foundation.infinitely-coherent-equivalences where

Imports
open import foundation.commuting-triangles-of-maps
open import foundation.dependent-pair-types
open import foundation.equivalences
open import foundation.function-types
open import foundation.homotopies
open import foundation.identity-types
open import foundation.propositions
open import foundation.retractions
open import foundation.sections
open import foundation.transposition-identifications-along-equivalences
open import foundation.universe-levels


Idea

An infinitely coherent equivalence e : A ≃∞ B from A to B consists of maps

  f : A → B
g : B → A


and for each x : A and y : B an infinitely coherent equivalence

  ∞-equiv-transpose-eq-∞-equiv : (f x ＝ y) ≃∞ (x ＝ g y).


Since this definition is infinite, it follows that for any x : A and y : B we have maps

  f' : (f x ＝ y) → (x ＝ g y)
g' : (x ＝ g y) → (f x ＝ y)


and for each p : f x ＝ y and q : g y ＝ x an infinitely coherent equivalence

∞-equiv-transpose-eq-∞-equiv : (f' p ＝ q) ≃∞ (p ＝ g' q).


In particular, we have identifications

  inv (f' x (f x) refl) : x = g (f x)
g' y (g y) refl : f (g y) ＝ y,


which are the usual homotopies witnessing that g is a retraction and a section of f. By infinitely imposing the structure of a coherent equivalence, we have stated an infinite hierarchy of coherence conditions. In other words, the infinite condition on infinitely coherent equivalences is a way of stating infinite coherence for equivalences.

Being an infinitely coherent equivalence is an inverse sequential limit of the diagram

  ... ---> is-finitely-coherent-equivalence 1 f ---> is-finitely-coherent-equivalence 0 f.


Definitions

The predicate of being an infinitely coherent equivalence

record is-∞-equiv
{l1 l2 : Level} {A : UU l1} {B : UU l2} (f : A → B) : UU (l1 ⊔ l2)
where
coinductive
field
map-inv-is-∞-equiv : B → A
map-transpose-is-∞-equiv :
(x : A) (y : B) → f x ＝ y → x ＝ map-inv-is-∞-equiv y
is-∞-equiv-map-transpose-is-∞-equiv :
(x : A) (y : B) → is-∞-equiv (map-transpose-is-∞-equiv x y)

open is-∞-equiv public


Infinitely coherent equivalences

record
∞-equiv
{l1 l2 : Level} (A : UU l1) (B : UU l2) : UU (l1 ⊔ l2)
where
coinductive
field
map-∞-equiv : A → B
map-inv-∞-equiv : B → A
∞-equiv-transpose-eq-∞-equiv :
(x : A) (y : B) → ∞-equiv (map-∞-equiv x ＝ y) (x ＝ map-inv-∞-equiv y)

open ∞-equiv public

module _
{l1 l2 : Level} (A : UU l1) (B : UU l2)
where

infix 6 _≃∞_

_≃∞_ : UU (l1 ⊔ l2)
_≃∞_ = ∞-equiv A B

∞-equiv-is-∞-equiv :
{l1 l2 : Level} {A : UU l1} {B : UU l2} {f : A → B} → is-∞-equiv f → A ≃∞ B
map-∞-equiv (∞-equiv-is-∞-equiv {f = f} H) = f
map-inv-∞-equiv (∞-equiv-is-∞-equiv H) = map-inv-is-∞-equiv H
∞-equiv-transpose-eq-∞-equiv (∞-equiv-is-∞-equiv H) x y =
∞-equiv-is-∞-equiv (is-∞-equiv-map-transpose-is-∞-equiv H x y)

map-transpose-eq-∞-equiv :
{l1 l2 : Level} {A : UU l1} {B : UU l2} (e : A ≃∞ B) →
(x : A) (y : B) → (map-∞-equiv e x ＝ y) → (x ＝ map-inv-∞-equiv e y)
map-transpose-eq-∞-equiv e x y =
map-∞-equiv (∞-equiv-transpose-eq-∞-equiv e x y)

is-∞-equiv-∞-equiv :
{l1 l2 : Level} {A : UU l1} {B : UU l2} (e : A ≃∞ B) →
is-∞-equiv (map-∞-equiv e)
map-inv-is-∞-equiv (is-∞-equiv-∞-equiv e) =
map-inv-∞-equiv e
map-transpose-is-∞-equiv (is-∞-equiv-∞-equiv e) =
map-transpose-eq-∞-equiv e
is-∞-equiv-map-transpose-is-∞-equiv (is-∞-equiv-∞-equiv e) x y =
is-∞-equiv-∞-equiv (∞-equiv-transpose-eq-∞-equiv e x y)

is-∞-equiv-map-transpose-eq-∞-equiv :
{l1 l2 : Level} {A : UU l1} {B : UU l2} (e : A ≃∞ B) (x : A) (y : B) →
is-∞-equiv (map-transpose-eq-∞-equiv e x y)
is-∞-equiv-map-transpose-eq-∞-equiv e x y =
is-∞-equiv-∞-equiv (∞-equiv-transpose-eq-∞-equiv e x y)


Infinitely coherent identity equivalences

is-∞-equiv-id : {l1 : Level} {A : UU l1} → is-∞-equiv (id {A = A})
map-inv-is-∞-equiv is-∞-equiv-id = id
map-transpose-is-∞-equiv is-∞-equiv-id x y = id
is-∞-equiv-map-transpose-is-∞-equiv is-∞-equiv-id x y = is-∞-equiv-id

id-∞-equiv : {l1 : Level} {A : UU l1} → A ≃∞ A
id-∞-equiv = ∞-equiv-is-∞-equiv is-∞-equiv-id


Composition of infinitely coherent equivalences

is-∞-equiv-comp :
{l1 l2 l3 : Level} {A : UU l1} {B : UU l2} {C : UU l3}
{g : B → C} {f : A → B}
(G : is-∞-equiv g)
(F : is-∞-equiv f) →
is-∞-equiv (g ∘ f)
map-inv-is-∞-equiv (is-∞-equiv-comp G F) =
map-inv-is-∞-equiv F ∘ map-inv-is-∞-equiv G
map-transpose-is-∞-equiv (is-∞-equiv-comp G F) x z p =
map-transpose-is-∞-equiv F x _ (map-transpose-is-∞-equiv G _ z p)
is-∞-equiv-map-transpose-is-∞-equiv (is-∞-equiv-comp G F) x z =
is-∞-equiv-comp
( is-∞-equiv-map-transpose-is-∞-equiv F x _)
( is-∞-equiv-map-transpose-is-∞-equiv G _ z)

comp-∞-equiv :
{l1 l2 l3 : Level} {A : UU l1} {B : UU l2} {C : UU l3} →
B ≃∞ C → A ≃∞ B → A ≃∞ C
comp-∞-equiv f e =
∞-equiv-is-∞-equiv
( is-∞-equiv-comp (is-∞-equiv-∞-equiv f) (is-∞-equiv-∞-equiv e))


Infinitely coherent equivalences obtained from equivalences

Since transposing identifications along an equivalence is an equivalence, it follows immediately that equivalences are infinitely coherent equivalences. This argument does not require function extensionality.

is-∞-equiv-is-equiv :
{l1 l2 : Level} {A : UU l1} {B : UU l2} {f : A → B} →
is-equiv f → is-∞-equiv f
map-inv-is-∞-equiv (is-∞-equiv-is-equiv H) =
map-inv-is-equiv H
map-transpose-is-∞-equiv (is-∞-equiv-is-equiv H) x y =
map-eq-transpose-equiv (_ , H)
is-∞-equiv-map-transpose-is-∞-equiv (is-∞-equiv-is-equiv H) x y =
is-∞-equiv-is-equiv (is-equiv-map-equiv (eq-transpose-equiv (_ , H) x y))

∞-equiv-equiv :
{l1 l2 : Level} {A : UU l1} {B : UU l2} → A ≃ B → A ≃∞ B
∞-equiv-equiv e =
∞-equiv-is-∞-equiv (is-∞-equiv-is-equiv (is-equiv-map-equiv e))


Properties

Any map homotopic to an infinitely coherent equivalence is an infinitely coherent equivalence

is-∞-equiv-htpy :
{l1 l2 : Level} {A : UU l1} {B : UU l2} {f g : A → B} →
f ~ g →
is-∞-equiv f → is-∞-equiv g
map-inv-is-∞-equiv (is-∞-equiv-htpy H K) =
map-inv-is-∞-equiv K
map-transpose-is-∞-equiv (is-∞-equiv-htpy H K) x y =
map-transpose-is-∞-equiv K x y ∘ concat (H x) _
is-∞-equiv-map-transpose-is-∞-equiv (is-∞-equiv-htpy H K) x y =
is-∞-equiv-comp
( is-∞-equiv-map-transpose-is-∞-equiv K x y)
( is-∞-equiv-is-equiv (is-equiv-concat (H x) _))


Homotopies of elements of type is-∞-equiv f

Consider a map f : A → B and consider two elements

  H K : is-∞-equiv f.


A homotopy of elments of type is-∞-equiv from H := (h , s , H') to K := (k , t , K') consists of a homotopy

  α₀ : h ~ k,


for each x : A and y : B a homotopy α₁ witnessing that the triangle

               (f x = y)
/         \
s x y /           \ t x y
/             \
∨               ∨
(x = h y) --------------> (x = k y)
p ↦ p ∙ α₀ y


commutes, and finally a homotopy of elements of type

  is-infinitely-coherent-equivalence
( is-∞-equiv-htpy α₁
( is-∞-equiv-comp
( is-∞-equiv-is-equiv
( is-equiv-concat' _ (α₀ y)))
( H' x y))
( K' x y).


In other words, there are by the previous data two witnesses of the fact that t x y is an infinitely coherent equivalence. The second (easiest) element is the given element K' x y. The first element is from the homotopy witnessing that the above triangle commutes. On the left we compose two infinitely coherent equivalences, which results in an infinitely coherent equivalence, and the element witnessing that the composite is an infinitely coherent equivalence transports along the homotopy to a new element witnessing that t x y is an infinitely coherent equivalence.

record
htpy-is-∞-equiv
{l1 l2 : Level} {A : UU l1} {B : UU l2} (f : A → B)
(H K : is-∞-equiv f) : UU (l1 ⊔ l2)
where
coinductive
field
htpy-map-inv-htpy-is-∞-equiv :
map-inv-is-∞-equiv H ~ map-inv-is-∞-equiv K
htpy-map-transpose-htpy-is-∞-equiv :
(x : A) (y : B) →
coherence-triangle-maps
( map-transpose-is-∞-equiv K x y)
( concat' _ (htpy-map-inv-htpy-is-∞-equiv y))
( map-transpose-is-∞-equiv H x y)
infinitely-htpy-htpy-is-∞-equiv :
(x : A) (y : B) →
htpy-is-∞-equiv
( map-transpose-is-∞-equiv K x y)
( is-∞-equiv-htpy
( inv-htpy (htpy-map-transpose-htpy-is-∞-equiv x y))
( is-∞-equiv-comp
( is-∞-equiv-is-equiv (is-equiv-concat' _ _))
( is-∞-equiv-map-transpose-is-∞-equiv H x y)))
( is-∞-equiv-map-transpose-is-∞-equiv K x y)


Being an infinitely coherent equivalence implies being an equivalence

module _
{l1 l2 : Level} {A : UU l1} {B : UU l2} {f : A → B}
where

is-equiv-is-∞-equiv : is-∞-equiv f → is-equiv f
is-equiv-is-∞-equiv H =
is-equiv-is-invertible
( map-inv-is-∞-equiv H)
( λ y →
map-inv-is-∞-equiv (is-∞-equiv-map-transpose-is-∞-equiv H _ y) refl)
( λ x → inv (map-transpose-is-∞-equiv H x (f x) refl))


Computing the type is-∞-equiv f

type-compute-is-∞-equiv :
{l1 l2 : Level} {A : UU l1} {B : UU l2} (f : A → B) → UU (l1 ⊔ l2)
type-compute-is-∞-equiv {A = A} {B} f =
Σ (B → A) (λ g → (x : A) (y : B) → Σ ((f x ＝ y) → (x ＝ g y)) is-∞-equiv)

map-compute-is-∞-equiv :
{l1 l2 : Level} {A : UU l1} {B : UU l2} (f : A → B) →
type-compute-is-∞-equiv f → is-∞-equiv f
map-inv-is-∞-equiv (map-compute-is-∞-equiv f H) =
pr1 H
map-transpose-is-∞-equiv (map-compute-is-∞-equiv f H) x y =
pr1 (pr2 H x y)
is-∞-equiv-map-transpose-is-∞-equiv (map-compute-is-∞-equiv f H) x y =
pr2 (pr2 H x y)

map-inv-compute-is-∞-equiv :
{l1 l2 : Level} {A : UU l1} {B : UU l2} (f : A → B) →
is-∞-equiv f → type-compute-is-∞-equiv f
pr1 (map-inv-compute-is-∞-equiv f H) =
map-inv-is-∞-equiv H
pr1 (pr2 (map-inv-compute-is-∞-equiv f H) x y) =
map-transpose-is-∞-equiv H x y
pr2 (pr2 (map-inv-compute-is-∞-equiv f H) x y) =
is-∞-equiv-map-transpose-is-∞-equiv H x y


Being an infinitely coherent equivalence is a property

is-prop-is-∞-equiv :
{l1 l2 : Level} {A : UU l1} {B : UU l2} (f : A → B) →
is-prop (is-∞-equiv f)
is-prop-is-∞-equiv = {!!}